2012
DOI: 10.1155/2012/152414
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Perforation in a Child with Crohn's Disease: Successful Medical Treatment Rescues from Colectomy

Abstract: Background. The challenging treatment of penetrating paediatric Crohn's disease (CD) involves pharmacological and surgical approaches. Despite a proved efficacy of anti-TNF agents for treatment of complex fistula, a large number of patients cannot achieve a complete healing and relapse during the followup. Aim. We report a paediatric case with CD and colonic perforation who was successfully treated with medical therapy only, including anti-TNFα. Case Presentation. During a colonoscopy performed on a 9-year-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…It is more frequent in the elderly with history of constipation and older than 60 years of age [ 1 4 ]. There are studies that showed perforated Meckel diverticulum in a 3-day-old neonate and a 9-year-old female patient with perforated Crohn’s disease [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is more frequent in the elderly with history of constipation and older than 60 years of age [ 1 4 ]. There are studies that showed perforated Meckel diverticulum in a 3-day-old neonate and a 9-year-old female patient with perforated Crohn’s disease [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%